Analyzing Islamic School Students’ English Vocabulary Learning: Motivation and Learning Strategies - Hidayatullah, Rahmad; Nugraheni, Dyah Ayu; Fauzi, Fatih Al (Universitas Nurul Jadid, 2025)
This study aims to analyze English vocabulary learning among Islamic middle school students particularly on their motivation and the learning strategies. A mixed methods approach was used, combining quantitative and qualitative approaches. Quantitatively, researchers used questionnaires to measure students' motivation in learning vocabulary. Qualitatively, in-depth interviews were conducted to understand students' experiences in learning English vocabulary. Quantitative data was collected through motivation and learning strategy questionnaires adapted from Tanaka's (2017) language learning model and distributed to 21 students. Qualitative data were gathered through semi-structured interviews with three students in the class. The results show that students with high intrinsic and extrinsic motivation tend to use more varied and active vocabulary learning strategies, such as intensive reading and using new vocabulary in conversational contexts. This finding is supported by data showing students' response percentages regarding their learning strategies. Generally, interactive and contextual learning strategies lead to better vocabulary mastery than passive strategies. This study suggests that further research should explore the relationship between learning motivation, learning strategies, and students' academic achievement in a broader context. Future studies are also recommended to involve entire classes without separating gender to achieve more representative results.